Multi-Omics and Targeted Approaches to Determine the Role of Cellular Proteases in Streptomyces Protein Secretion - Busche, Tobias; Tsolis, Konstantinos C.; Koepff, Joachim; Rebets, Yuriy; Rückert, Christian; Hamed, Mohamed B.; Bleidt, Arne; Wiechert, Wolfgang; Lopatniuk, Mariia; Yousra, Ahmed; Anné, Jozef; Karamanou, Spyridoula; et al. (Frontiers in Microbiology, 2018)
Gram positive Streptomyces bacteria are profuse secretors of polypeptides using complex, yet unknown mechanisms. Many of their secretory proteins are proteases that play important roles in the acquisition of amino acids from the environment. Other proteases regulate cellular proteostasis. To begin dissecting the possible role of proteases in Streptomyces secretion, we applied a multi-omics approach. We probed the role of the 190 proteases of Streptomyces lividans strain TK24 in protein secretion in defined media at different stages of growth. Transcriptomics analysis revealed transcripts for 93% of these proteases and identified that 41 of them showed high abundance. Proteomics analysis identified 57 membrane-embedded or secreted proteases with variations in their abundance. We focused on 17 of these proteases and putative inhibitors and generated strains deleted of their genes. These were characterized in terms of their fitness, transcriptome and secretome changes. In addition, we performed a targeted analysis in deletion strains that also carried a secretion competent mRFP. One strain, carrying a deletion of the gene for the regulatory protease FtsH, showed significant global changes in overall transcription and enhanced secretome and secreted mRFP levels. These data provide a first multi-omics effort to characterize the complex regulatory mechanisms of protein secretion in Streptomyces lividans and lay the foundations for future rational manipulation of this process.